Resepsi Hadis Dalam Film Animasi "Jangan Menuduh" Pada Kanal YouTube NussaOfficial - Fitri Sari (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2024)
Previously, hadiths were only studied within the educational environment of Islamic schools or religious boarding schools (Pesantren). However, with the advancement of media today, hadith has become widely accessible through various media, Including YouTube platform in the form of visual videos such as animated films. This study aims to analyse the reception of hadith in the animated film "Jangan Menuduh" presented on the NussaOfficial YouTube channel. Employing a qualitative descriptive approach and analysis using Ahmad Rafiq's reception theory, which categorises reception into three forms: exegetical, aesthetic, and functional, this research explores how creative approaches in delivering religious teachings through animated films prove effective in conveying moral messages to its audience. Within the context of the film, reception of hadith manifests in three forms: firstly, exegetical reception, where the character Uma reads and interprets the hadith text literally to provide advice to her son Rarra. Secondly, aesthetic reception, where the visual presentation of the hadith text is showcased in an aesthetically pleasing manner through Islamic-themed animation. Thirdly, functional reception, where the hadith text is understood and transformed for the audience's benefit.